Penggunaan Bahasa dalam Spanduk Iklan Partai Politik Periode 2014-2019 di Lombok Timur - Muh. Irfan (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2019)
The research is aimed to investigate the type of diction and language style which used in political party banner advertisement in East Lombok. This research was descriptive qualitative to get some basic information about the diction and language style which used in banner advertisement political party in East Lombok. To collect the data, the researcher used documentation which includes book, newspaper, magazine, photo or picture in order to find out the source. The data were a photo of a political party banner advertisement in East Lombok. The data were analyzed by using textual analysis with particular criteria which concerned with analyzing the language element in the political party banner advertisement in East Lombok. Based on the analysis result there are some findings. The diction used political party banner advertisement in East Lombok were connotative and denotative. The language style used was alliterated, assonance, personification, and hyperbole. After all the hyperbole style was dominated.